The relationship of gene polymorphism with the heart failure risk in patients with hypertension and high adherence to treatment - N. A. Koziolova; A. I. Chernyavina (Российский кардиологический журнал, 2020)
Aim. To determine the heart failure (HF) risk in patients with hypertension (HTN) and high adherence to treatment, depending on the blood concentration of the N-terminal pro-brain natriuretic peptide (NT-proBNP) and gene polymorphism.Material and methods. The study included 232 patients with HTN without a verified diagnosis of HF. The mean age was 46,13±8,21 years. Patients were evaluated for genotypes by following markers: AGT Thr174Met rs4762, GNB3 C825T rs5443, MTHFR C677T rs1801133, MTRR Ile22Met rs1801394, ApoE Cys130Arg rs 429358, PPARα G/C rs425377. We also assessed ejection fraction, diastolic function and left ventricular mass index by echocardiography and determined NT-proBNP blood levels. Patients were divided into two groups depending on the NT-proBNP concentration. The group 1 consisted of 64 (27,6%) patients with NT-proBNP >125 pg/ml, the group 2 — 168 (72,4%) patients with NT-proBNP <125 pg/ml.Results. Among patients with NT-proBNP >125 pg/ml, the most significant was the C/T genotype of MTHFR C677T polymorphism (rs1801133), 95% confidence interval (CI) for the odds ratio (OR) and relative risk (RR) of HF was 4,82 and 3,29, respectively (95% CI for OR=2,24-10,60; for OR=1,80-6,39). The A/G and G/G genotypes of the MTRR Ile22Met polymorphism (rs1801394) were statistically significant. The probability of HF with the A/G genotype of the MTRR gene increased by more than 2 times (OR=2,32, 95% CI=1,15-4,64), and the OR of its development was 1,77 (95% CI=1,11-2,69). The probability of HF with the G/G genotype increased more than 3 times (OR=3,65, 95% CI=1,37-9,76), and the OR of its development was 2,20 (95% CI=1,25-3,27). Correlation analysis revealed a direct relationship between the NTproBNP levels and polymorphism of the MTHFR (r=0,47; p<0,005) and MTRR (r=0,33; p<0,05) genes.Conclusion. In patients with HTN and high adherence to treatment, the HF risk with an Nt-proBNP >125 pg/ml depends on genetic determinism. Candidate genes for the HF in HTN patients with high adherence to treatment are the genotypes C/T of MTHFR C677T polymorphism (rs1801133), and A/G and G/G of MTRR Ile22Met polymorphism (rs1801394).